Amino lactam and saccharic acid lactone modified lactide high polymer and preparation method thereof

By introducing aminoamide and glycolitate units in polystumin, and using alkaline amino acid and phenylalanate zinc as a catalyst, the problem of long degradation cycle, poor toughness, and high acidic acid degradation cycles of lactic acid have been solved. The faster degradation speed, higher toughness and neutral degradation products have expanded its application in the field of biomedical.

CN119371654APending Publication Date: 2025-01-28ZHONG DING KAI RUI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411487985.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The degradation period of polylactic acid is too long, the toughness is poor, the degradation product is highly acidic, and the existing catalysts have toxicity problems.

Method used

Using aminamide and glycolitate to modify the propylene hypercin, by introducing amino-amino acid units, glycogen acid or glycal aldehyde, and lactic acid units, alkaline amino acids and zinc benate as catalysts can be used to improve the polymer The degradation performance, toughness and the pH of the lactic acid.

Benefits of technology

It improves the degradation speed and toughness of polylactic acid, the pH of the degradation products tends to be neutral, avoids stimulation of the tissue, and replaces the toxic tin catalyst, and broaden its application scenarios in the field of biomedical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099206480000051
    Figure BDA0005099206480000051
  • Figure BDA0005099206480000061
    Figure BDA0005099206480000061
  • Figure BDA0005099206480000073
    Figure BDA0005099206480000073
Patent Text Reader

Abstract

The invention belongs to the field of modification of biodegradable materials, and particularly relates to an amino lactam and saccharic acid lactone modified lactide high polymer and a preparation method thereof. According to the invention, gulonic acid-gamma-lactone, galactolactone, D-galacturonic acid lactone and the like are used as initiators and polymerization monomers, amino acid zinc is used as a catalyst, DL-aminocaprolactam, 2-amino-delta-valerolactam, (R)-3-amino-2-caprolactam and the like are used as polymer acid-base property adjusting monomers, and the acid-base property of the polymer is adjusted to obtain the polycaprolactam-galactolactone copolymer. The metal-toxicity-free high polymer containing an amino-amino acid unit, a saccharic acid ester or uronic acid ester unit and a lactic acid unit is formed through polymerization with lactic acid or lactide, so that the degradation performance and toughness of polylactic acid and the acid-base property of a degradation product are improved, and the application scene of polylactic acid is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biodegradable material modification, and in particular relates to a lactide polymer modified by aminolactam and saccharide lactone and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA), also known as polylactide, is a new type of biodegradable material made from starch raw materials from renewable plant resources (such as corn, etc.). The starch raw materials are made into lactic acid through a fermentation process, and then converted into polylactic acid through chemical synthesis. It has good biodegradability and can be completely degraded by microorganisms in nature after use, eventually generating carbon dioxide and water without polluting the environment. This is very beneficial to protecting the environment and is a recognized environmentally friendly material. The treatment method for ordinary plastics is still incineration, which causes a large amount of greenhouse gases to be discharged into the air, while polylactic acid plastics are buried in the soil for degradation, and the carbon dioxide produced directly enters the soil organic matter or is absorbed by plants, and will not be discharged into the air, and will not cause a greenhouse effect.

[0003] Polylactic acid has good compatibility and degradability. The biomedical industry is the earliest field where polylactic acid has been applied. Polylactic acid is highly safe for the human body and can be absorbed by tissues. In addition to its excellent physical and mechanical properties, it can also be used in the biomedical field, such as disposable infusion tools, non-disassembly surgical sutures, drug relief packaging agents, artificial fracture internal fixation materials, tissue repair materials, artificial skin, etc. High molecular weight polylactic acid has very high mechanical properties. It has been used to replace stainless steel in Europe and the United States. It is widely used as a new type of orthopedic internal fixation material such as bone nails and bone plates. Its ability to be absorbed and metabolized by the human body saves patients from the pain of secondary surgery. It has high technical added value and is a polymer material with development prospects in the medical industry.

[0004] The synthesis of polylactic acid generally has ⑴ direct polycondensation method: using solvent to dehydrate and polycondense under vacuum. Japan has done a lot of research in this regard, but ultimately failed to achieve industrialization. ⑵ Two-step method: lactic acid generates cyclic dimer lactide, and then ring-opening polycondenses to polylactic acid. This technology is relatively mature, and the process of producing polylactic acid by NatureWorks in the United States is this process. ⑶ Reaction extrusion to prepare high molecular weight polylactic acid, using a combination of an intermittent stirred reactor and a twin-screw extruder, and conducting a continuous melt polymerization experiment, a polylactic acid with a molecular weight of 150,000 obtained by continuous melt polycondensation of lactic acid can be obtained. The low molar mass lactic acid prepolymer is further polycondensed on the extruder using a twin-screw extruder to prepare a higher molar mass polylactic acid. When the reaction temperature is 150°C, the catalyst dosage is 0.5%, and the screw speed is 75r / min, the molar mass of polylactic acid can be quickly and effectively increased by the twin-screw reaction extrusion polycondensation method, and the dispersion coefficient of the reaction extrusion product is reduced and the uniformity is improved. By comparing the DSC curves, it is found that the crystallinity of polylactic acid produced by the reaction extrusion polycondensation method is reduced, which is beneficial to improving the brittleness of polylactic acid materials during use. However, the reaction caused by high-temperature extrusion will increase the corrosion of polylactic acid on the extruder screw, and the metal ions that fall off from the corrosion will adhere to the surface of polylactic acid and mix into the melt as the twin screws rotate and shear. The purity of the product will be reduced and the content of heavy metal ions will increase.

[0005] PLA has a tensile strength of 40-60MPa and an elongation at break of 4-10%. Its degradation cycle varies according to its structure. For example, the degradation cycle of DL-PLA is 12-16 months, while the degradation cycle of L-PLA is more than 24 months.

[0006] The performance of polylactic acid as a medical material has the following problems:

[0007] (1) The degradation cycle is too long, 12-24 months, which does not match the repair and recovery cycle of soft and hard tissues. It is necessary to increase its degradation rate and shorten the degradation cycle; (2) The elongation at break of PLA is only 4-10%, and its toughness is poor, which needs to be improved. (3) The degradation product is lactic acid, which is acidic and has a pH as low as 2.5, which is quite different from tissue fluid (7.35-7.45). It will cause irritation and verification reactions, which is not conducive to tissue wound recovery.

[0008] Therefore, there is a need in the art to modify polylactic acid.

[0009] In addition, although the currently used stannous octoate catalysts have high catalytic efficiency and can produce high molecular weight PLA with excellent performance, they are toxic and have serious side effects such as poisoning when tin ions enter the blood. The selection of new catalysts is also one of the top priorities for the synthesis of medical PLA. Summary of the invention

[0010] In order to solve the above problems, the present invention provides a high-activity aminolactam sugar acid lactone modified lactide polymer and a preparation method thereof, which uses gulonic acid-γ-lactone, galactonic acid lactone and D-galacturonic acid lactone as initiators and polymerization monomers, amino acid zinc as a catalyst, and uses DL-aminocaprolactam, 2-amino-δ-valerolactam, (R)-3-amino-2-caprolactam and the like as polymer acid-base adjustment monomers, and forms a metal-free polymer containing amino-amino acid units, sugar acid or uronic acid units and lactic acid units through polymerization with lactic acid or lactide, thereby improving the degradation performance and toughness of PLA and the acidity and alkalinity of the degradation products, and broadening its application scenarios.

[0011] Specifically, in one aspect, the present invention provides an aminolactam and saccharide lactone modified lactide polymer, which is polymerized by lactic acid or lactide as the first monomer, aminolactam as the second monomer and saccharide lactone or uronic acid lactone as the third monomer, and its main chain contains lactic acid units, amino-amino acid units and saccharide esters or uronic acid esters units.

[0012] Furthermore, the lactide polymer contains 98-70 mol% of lactic acid units, 1-15 mol% of amino-amino acid units, and 1-15 mol% of sugar ester or uronic acid ester units.

[0013] Furthermore, the lactic acid or lactide includes at least one of D-lactic acid, L-lactic acid, DL-lactic acid; D-lactide, L-lactide, and DL-lactide.

[0014] Furthermore, the aminolactam includes at least one of DL-aminocaprolactam, 2-amino-δ-valerolactam, and (R)-3-amino-2-caprolactam.

[0015] Furthermore, the sugar acid lactone or sugar acid lactone includes at least one of D-(-)-gulonic acid-γ-lactone, D-galactonic acid lactone, L-galactonic acid-1,4-lactone, and D-galacturonic acid-γ-lactone.

[0016] In another aspect, the present invention provides a method for preparing the aminolactam and saccharolactone modified lactide polymer as described herein, comprising the following steps:

[0017] (1) Preparation of the catalyst: using basic amino acid, phenylalanine and zinc salt as raw materials to prepare a zinc complex of basic amino acid and phenylalanine;

[0018] (2) Preparation of modified lactide polymer: Lactic acid or lactide as the first monomer, aminolactam as the second monomer, saccharide lactone or uronic acid lactone as the third monomer and the catalyst obtained in step (1) are added to a reaction kettle under the protection of nitrogen or inert gas, and reacted at 120-180° C. for 6-100 hours to obtain a lactide polymer modified by aminolactam and saccharide lactone.

[0019] Furthermore, the basic amino acid is at least one of lysine, histidine and arginine.

[0020] Furthermore, the zinc salt is zinc chloride or zinc sulfate.

[0021] Furthermore, the preparation of the catalyst in step (1) specifically comprises: reacting a basic amino acid and phenylalanine with an inorganic guanidine salt in a solvent at 50-80° C. under the protection of nitrogen or an inert gas to generate an organic guanidine salt of the basic amino acid and phenylalanine, and then adding a water and / or alcohol solution of a zinc salt, reacting at 50-80° C. for 3-8 hours to obtain a zinc complex of the basic amino acid and phenylalanine.

[0022] Furthermore, in step (1), the ratio of the total amount of basic amino acids and phenylalanine to the solvent is 1 (mol): 1-2 (L).

[0023] Furthermore, in step (1), the molar ratio of the basic amino acid to phenylalanine is 1:0.8-1.2.

[0024] Furthermore, in step (1), the molar ratio of the total amount of basic amino acids and phenylalanine to the inorganic guanidine salt is 1:0.5-1.2.

[0025] Furthermore, in step (1), the molar ratio of the total amount of basic amino acids and phenylalanine to the zinc salt is 2:1.

[0026] Furthermore, the solvent in step (1) is at least one of water, methanol, ethanol, tetrahydrofuran and dioxane.

[0027] Furthermore, the inorganic guanidine salt in step (1) is guanidine carbonate.

[0028] Furthermore, the concentration of the zinc salt in water and / or alcohol solution is 0.2-1.5 mol / L, preferably 0.5-1.0 mol / L.

[0029] Furthermore, step (1) also includes filtering, collecting, washing and drying the obtained zinc complex of basic amino acid and phenylalanine.

[0030] Furthermore, in step (2), the molar ratio of lactic acid or lactide as the first monomer, aminolactam as the second monomer, and saccharide lactone or uronic acid lactone as the third monomer is 98-70:1-15:1-15.

[0031] Furthermore, in step (2), the mass of the catalyst is 0.4-1.0% of the mass of the monomer.

[0032] Furthermore, the lactic acid or lactide includes at least one of D-lactic acid, L-lactic acid, DL-lactic acid; D-lactide, L-lactide, and DL-lactide.

[0033] Furthermore, the aminolactam includes at least one of DL-aminocaprolactam, 2-amino-δ-valerolactam, and (R)-3-amino-2-caprolactam.

[0034] Furthermore, the sugar acid lactone or sugar acid lactone includes at least one of D-(-)-gulonic acid-γ-lactone, D-galactonic acid lactone, L-galactonic acid-1,4-lactone, and D-galacturonic acid-γ-lactone.

[0035] Furthermore, the step (2) is carried out in an anhydrous and oxygen-free environment.

[0036] Furthermore, before the heating reaction in step (2), the reaction kettle is evacuated. Furthermore, the vacuum is evacuated to a vacuum degree of less than 50Pa.

[0037] Furthermore, the reaction in step (2) is preferably carried out at 130-140° C., and the reaction time is preferably 16-32 hours.

[0038] Further, the reaction comprises reacting at 120-150° C. for 2-4 hours, and then heating to 130-160° C. for 5-15 hours.

[0039] Furthermore, step (2) further comprises adding a non-protonic solvent to the reactor to dissolve the harvested aminolactam and lactide polymer modified with saccharide lactone, and then precipitating and washing the polymer with a polar solvent and drying it.

[0040] Furthermore, the aprotic solvent includes 1,2-dichloroethane, chloroform, dichloromethane, etc., and the amount thereof is 1 g (polymer) / 5-10 ml (solvent).

[0041] Furthermore, the polar solvent includes methanol, ethanol, tetrahydrofuran, dioxane and the like.

[0042] In other aspects, the present invention also provides the use of the aminolactam- and saccharolactone-modified lactide polymers as described herein as biodegradable materials in the biomedical field.

[0043] In other aspects, the present invention also provides an amino acid zinc complex used as a catalyst for the ring-opening polymerization of lactide and lactone, which is prepared as follows: a zinc complex of basic amino acid and phenylalanine is prepared using basic amino acid, phenylalanine and zinc salt as raw materials.

[0044] Furthermore, the basic amino acid is at least one of lysine, histidine and arginine, and the zinc salt is zinc chloride or zinc sulfate.

[0045] Furthermore, the preparation of the catalyst specifically includes: under the protection of nitrogen or inert gas, reacting basic amino acids and phenylalanine with inorganic guanidine salts in a solvent at 50-80° C. to generate organic guanidine salts of basic amino acids and phenylalanine, and then adding a water and / or alcohol solution of a zinc salt, reacting at 50-80° C. for 3-8 hours to obtain a zinc complex of the basic amino acid and phenylalanine.

[0046] Furthermore, the ratio of the total amount of basic amino acids and phenylalanine to the solvent is 1 (mol): 1-2 (L).

[0047] Furthermore, the molar ratio of the basic amino acid to phenylalanine is 1:0.8-1.2.

[0048] Furthermore, the molar ratio of the total amount of basic amino acids and phenylalanine to the inorganic guanidine salt is 1:0.5-1.2.

[0049] Furthermore, the molar ratio of the total amount of basic amino acids and phenylalanine to the zinc salt is 2:1.

[0050] Furthermore, the solvent is at least one of water, methanol, ethanol, tetrahydrofuran and dioxane.

[0051] Furthermore, the inorganic guanidine salt is guanidine carbonate.

[0052] Furthermore, the method also includes filtering, collecting, washing and drying the obtained zinc complex of the basic amino acid and phenylalanine.

[0053] In other aspects, the present invention also provides the use of the amino acid zinc complex as described herein as a catalyst for the ring-opening polymerization of lactides and lactones.

[0054] Beneficial effects of the present invention

[0055] The present invention increases the polarity and degradation rate of polylactic acid by introducing a sugar acid lactone unit, which can adapt to the tissue repair cycle, introduces amino lactam so that the pH of its degradation product increases to 6.0-7.0 and tends to be neutral, which can avoid the stimulation of the degradation acid product to the tissue; uses basic amino acids and zinc phenylalanine catalysts to replace stannous octoate catalysts, avoiding the toxicity of tin; improves the toughness of polylactic acid through the ternary structure, so that it has a higher elongation at break, and can avoid the problem of fracture due to stress concentration or local stress. The strength of the high-activity sugar acid lactone lactide polymer provided by the present invention has an early vacancy support function, gradual degradation and tissue fusion, and is absorbed and replaced by the tissue. The degradation component can provide a variety of organic components that promote tissue regeneration, improve the regeneration and reconstruction function of the tissue; its degradation rate can be controlled according to the composition, matching with tissue regeneration and reconstruction. During use, it will reduce surgical infections caused by bacterial infection and inflammation such as redness, swelling, exudation, etc., and can be widely used in tissue trauma, defects, fixation and isolation. DETAILED DESCRIPTION

[0056] In an exemplary embodiment, the present invention contemplates a polymer having the following structure:

[0057]

[0058] Structure (I): Lactide is used as the starting monomer for polymerization

[0059]

[0060] Structure (II): Lactic acid is used as the starting monomer for polymerization.

[0061] In the above structural formula, A is a lactide or lactic acid unit. Regardless of whether lactide or lactic acid is used as the starting material, the polymer after ring-opening polymerization is lactic acid unit. B is an aminolactam unit (amino-amino acid unit after ring opening), and C is a sugar acid lactone unit structure or a uronic acid unit (sugar ester or uronic acid ester unit after ring opening). The selection range of A, B, and C is as follows:

[0062] A optional monomer is: D-lactic acid L-Lactic Acid DL-lactic acid D-Lactide L-Lactide DL-Lactide wait.

[0063] B optional monomer is: DL-aminocaprolactam 2-Amino-δ-valerolactam (R)-3-Amino-2-caprolactam wait.

[0064] C optional monomer is: D-(-)-gulonic acid-γ-lactone D-Galactone L-galactonic acid-1,4-lactone D-galacturonic acid-γ-lactone

[0066] The A content is 98-70 mol%; the B content is 1-15 mol%; and the C content is 1-15 mol%.

[0067] Since obtaining high molecular weight PLA requires an efficient catalyst, and commonly used tin compounds such as stannous octoate have strong toxicity and are difficult to separate from polymers, the present invention needs to prepare a class of non-toxic, tissue-friendly amino acid zinc catalysts. For this reason, the present invention will use amino acid zinc as a catalyst for synthesizing highly active saccharolactone lactide polymers. In order not to reduce the acidity of the polymer, the present invention uses basic amino acids (i.e., using lysine, arginine, histidine) and phenylalanine as units of the catalyst, as a chelating agent for zinc. The preparation route is as follows:

[0068]

[0069] The arginine in the above schematic route can be replaced by lysine or histidine, but phenylalanine cannot be replaced. The basic amino acid is selected from the following amino acid monomers: Lysine, Histidine, Arginine.

[0070] The amino acid is dissolved in methanol, heated to 50-80°C, and guanidine carbonate is added under stirring conditions to make the amino acid generate an organic guanidine salt dissolved in methanol, that is, an amino acid salt solution; the molar ratio of guanidine carbonate to amino acid is 0.5-1.0:1; further, the amino acid salt reacts with zinc sulfate or zinc chloride to generate an amino acid zinc complex; a methanol solution of zinc salt is added dropwise to the amino acid salt solution, and the reaction is carried out under a nitrogen or inert gas atmosphere and a temperature of 50-80°C for 5 hours to obtain the amino acid zinc complex. The molar ratio of amino acid to zinc salt is 2:1. The amino acid zinc complex can be used as a catalyst for the ring-opening polymerization of lactide or lactone, wherein the polymerization is homopolymerization or copolymerization, wherein the polymerization monomer in the homopolymerization is one or more of lactide, caprolactone, valerolactone, saccharolactone, uronic acid lactone, and aminolactam, the product of the lactide homopolymerization is polylactic acid, the product of the saccharolactone homopolymerization is a saccharate or uronic acid ester structure embedded between lactic acid structures; the product of the aminolactam homopolymerization is an amino acid unit embedded between lactic acid units.

[0071] Furthermore, alcohols are generally used as initiators for lactide polymerization, such as benzyl alcohol, cyclohexyl sterol, etc. These initiators are highly effective in initiating ring-opening polymerization, but they need to be removed after the polymerization is completed if they are mixed in the polymer, otherwise the polymer properties will be affected. However, the polymer is sensitive to water and cannot be washed with water. Washing with other solvents will increase both the process and the cost. Therefore, gulonic acid-γ-lactone, galactonic acid lactone and D-galacturonan lactone are selected as initiators, which can be used as both initiators and polymerization monomers to increase the hydrophilicity and polarity of the polymer. The degradation rate of the polymer in aqueous solutions such as blood, tissue fluid and other environments will be accelerated, and its toughness will also increase due to the presence of comonomers.

[0072] Furthermore, aminolactams will also open their rings under the action of initiators or catalysts to form amino acid unit structures with side chain amino groups. Due to the presence of amino groups, these units have a certain alkalinity, which can reduce the acidity of lactic acid, increase the pH value after degradation, and reduce the stimulation of acidity on cell nuclear tissues. At the same time, a small amount of amide structure can enhance the strength and toughness of the polymer, improve the mechanical properties of the polymer, and meet the requirements for fixation or suturing.

[0073] Further, the lactide is one or more of L-lactide, D-lactide, and DL-lactide, and one or more of saccharolactone, uronic acid lactone, and aminolactam are mixed, and the polymerization method adopted is a bulk polymerization method of homopolymerization and copolymerization. The specific steps are: under anhydrous and anaerobic conditions, the three types of monomers and amino acid zinc complexes are added in a selected set ratio, the reaction temperature is 120-180°C, preferably 130-140°C, and the reaction time is 6-100 hours, preferably 16-32 hours. Since zinc chloride or zinc sulfate is easily hydrolyzed, the zinc salt solution must be prepared and used immediately, and the concentration of zinc chloride methanol or aqueous solution is set to 0.2-1.5 mol / L, preferably 0.5-1.0 mol / L, and the reaction process of the present invention should be carried out in an inert gas environment.

[0074] Further, the polymerization reaction needs to be in a vacuum anhydrous and oxygen-free environment, and the polymer container needs to be dehydrated and deoxygenated. The present invention will use a reactor that can be continuously evacuated, and the reactor uses a ceramic liner. A reactor with a volume of 5.0L with heating and a ceramic liner is used. The reactor has an outlet for high-purity nitrogen or argon interface, a vacuum interface (T-interface, closed after the vacuum degree reaches the requirement, and opened when needed), a thermocouple temperature display, online monitoring of the reaction temperature, and a magnetic stirrer that can stir in the liquid state to ensure the uniformity of material distribution in the liquid system.

[0075] Further, after the polymerization is completed, a non-protonic solvent is used to dissolve and purify the polymer, and the selected solvent is 1,2-dichloroethane, chloroform, dichloromethane, etc., and the amount thereof is 1g (polymer) / 5-10ml (solvent). After the polymerization is completed, when the polymer cools to room temperature, the solvent is injected into the reactor, and after it is completely dissolved, the polymer solution is discharged from the discharge port, and then a polar solvent such as methanol, ethanol, tetrahydrofuran, and dioxane is added to precipitate the polymer, and the solvent is washed 5-8 times and then placed in a high vacuum oven for drying, the drying temperature is 60-80°C, and the drying time is 6-18 hours, preferably 8-12 hours.

[0076] Furthermore, the present invention uses basic amino acids and zinc phenylalanine as catalysts for the ring-opening polymerization of lactide and lactone, which has the advantages of low catalyst dosage (only 0.4-1.0% of the monomer mass), high yield (75-95%), and very high product molecular weight; the basic amino acids and zinc phenylalanine prepared by the present invention are used as catalysts for the ring-opening polymerization of glycolide, lactide, caprolactone, valerolactone, and trimethylene carbonate, which have the characteristics of fast polymerization reaction speed, high product molecular weight, and suitability for bulk polymerization. Since basic amino acids and zinc phenylalanine have the advantages of promoting tissue regeneration and being non-toxic, they can be left in the polymer as nutrients after polymerization, and do not need to be separated, thereby simplifying the polymerization process and reducing production costs.

[0077] More specifically, in order to obtain a highly active lactone lactide polymer having structures (I) and (II), the present invention will provide the following technical methods to gradually obtain the target polymer. The first key technology provided by the present invention is the preparation of basic amino acids and zinc phenylalanine catalysts. Add basic amino acids and phenylalanine into a reactor with heating, stirring and nitrogen protection, add water, methanol, ethanol, tetrahydrofuran, dioxane and other solvents, the ratio of the total amount of amino acids to the solvent is 1 (mol): 1-2L; the molar ratio of basic amino acids to phenylalanine is 1: 0.8-1.2. Then add guanidine carbonate, the molar ratio of guanidine carbonate to the total amount of amino acids is 0.5-1.0: 1; then heat to 50-80°C under nitrogen protection, and form a transparent solution after about 30 minutes. Further, zinc chloride or zinc sulfate is configured into water or methanol solution and added to the above solution, react with 50-80°C under nitrogen protection for 3-8 hours, then cool to room temperature, and filter to obtain a zinc complex of basic amino acids and phenylalanine. After washing twice with methanol, ethanol, tetrahydrofuran or dioxane, it was dried in a vacuum oven at 60°C for 12-24 hours.

[0078] Further, another key technology provided by the present invention is the process of the reaction of active sugar acid lactone lactide polymer. Before adding raw materials and catalysts, a 10L reactor with heating and ceramic liner is introduced with high-purity nitrogen and heated to 120°C, and high-purity nitrogen is continuously passed at this temperature for 15 minutes. Further, the T-interface is closed and the nitrogen is stopped. The temperature drops to 30-50°C, and then lactide, sugar acid lactone, aminolactam and basic amino acid and phenylalanine zinc complex are added by opening the feed port, and then the feed port is closed. Reopen the nitrogen, open the T-interface, and pass nitrogen for 15 minutes; further, close the T-interface, turn off the nitrogen, start vacuuming, when the vacuum degree is less than 50Pa, close the T-interface, start heating, when the temperature reaches 130-180°C, stop heating, and start stirring, and stop stirring after 20 minutes. Then react at 120-150°C for 2-4 hours, then heat to 130-160°C for 5-15 hours. After the polymerization is completed, the polymerization kettle is cooled to room temperature, and then 2-dichloroethane, trichloromethane, dichloromethane, etc. are added, and the amount is 1g (polymer) / 5-10ml (solvent). After complete dissolution, the polymer solution is transferred to a 10L stainless steel barrel, and a polar solvent such as methanol, ethanol, tetrahydrofuran, dioxane, etc. is used to precipitate the polymer, and the solvent is washed 5-8 times and placed in a high vacuum oven for drying. The drying temperature is 60-80°C, and the drying time is 6-18 hours, preferably 8-12 hours.

[0079] Furthermore, the dried polymer was micro-injected into mechanical specimens at 180-200° C. using a Haake rheometer.

[0080] Molecular weight test: The intrinsic viscosity is measured at 37±0.1℃, the formula is as follows: η=[2(η sp –lnηr)] 1 / 2 / C. C is the viscosity of the polymer solution (g / L); η r is the relative viscosity, dilute solution = t / t0; η sp is the specific viscosity, η sp =η r -1. η=KMα, calculate the viscosity average molecular weight of polylactic acid (where K=1.04×10-4, α=0.75); molecular weight distribution is tested by GPC, and the solvent is THF.

[0081] (1) Determination of molecular weight The molecular weight of polylactic acid (PLA) was determined by viscosity method. Accurately weigh a certain amount of product (about 0.080-0.1009), dissolve it in a 100mL volumetric flask with THF, and shake overnight. Use an Ubbelohde viscometer with a capillary diameter of 0.46mm in a 37.°C constant temperature water bath to measure its outflow time t, measure the outflow time to of the pure solvent, and use the one-point method to calculate the intrinsic viscosity of PLA. (2) Determination of molecular weight distribution The molecular weight distribution was carried out on a Water 410 gel chromatography analyzer, the solvent was THF, the mobile phase outflow rate was 1.00mL / min, and the temperature was 35°C.

[0082] Thermal performance test: The thermal performance test was carried out using a DEC-7 differential scanning calorimeter (DSC) from Perkin-Elemer, USA, to determine the melting point (Tm), glass transition temperature (Tg), thermal decomposition temperature (Td) and crystallization temperature (Tc) of the PLA product. The starting temperature was set at 20°C, the heating rate was 10°C / min, and the nitrogen atmosphere was used.

[0083] Mechanical properties test: The tensile strength was measured according to GB13022-91 method.

[0084] Degradation test method: Take the injection molded material and conduct degradation test in PBS solution: The preparation method of PBS is as follows; accurately weigh KH2PO4 (0.544g), Na2HPO4·12H2O (7.16g), NaCl (16g) and KCl (0.402g) and dissolve them in 2L deionized water, use a volumetric flask to make up the volume, and the pH measurement range is between 7.2-7.4; put the sample into a centrifuge tube and add a certain amount of PBS solution, the volume ratio of PBS solution to sample mass is 1g / 30mL; then place the centrifuge tube containing the sample in a constant temperature oscillating box at a temperature of 37℃ and a speed of 80rpm / min; take out the sample at 1 (1D), 1w, 4w, 12w and 24w days, weigh it and calculate the weight loss rate. Set up three control groups for each sample.

[0085] pH determination: The supernatant of the sample was measured using a pH meter and PBS was replaced every 7 days.

[0086] Cytotoxicity and cell proliferation rate test: Prepare the extraction solution in accordance with the provisions of T16886 on biological materials, and calculate the proliferation rate by comparing the standard extract with the blank.

[0087] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0088] Embodiment 1:

[0089] (1) Catalyst preparation: Synthesis of L-arginine / L-phenylalanine zinc: Arginine (17.5 g, about 0.1 mol), L-phenylalanine (16.5 g, about 0.1 mol) and methanol (300 ml) were added to a 1 L three-necked flask, stirred and reacted in a constant temperature water bath at 60°C for 20 min, guanidine carbonate (24 g, about 0.2 mol) was added, and 50 ml of deionized water was added until all dissolved, then nitrogen was introduced into the solution for 10 min to remove oxygen in the solution and the reaction flask, and 100 ml of zinc chloride methanol water (methanol / water = 80 ml / 20 ml) solution (13.6 g, about 0.1 mol) was added in a nitrogen-filled environment, and after the addition was completed in 30 minutes, the mixture was reacted at 60°C for 5 hours, cooled to room temperature, filtered, and the precipitate was washed with ethanol 4 times, and the product was dried in a vacuum oven at 60°C for 24 hours to obtain 38 g. The moisture content after drying was less than 0.01%.

[0090] (2) Preparation of lactone lactide polymer: A 10L ceramic reactor with a heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously introduced at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 30-50°C, and then the feed port was opened to add dried L-lactide (907g), L-gulonic acid-γ-lactone (50g), DL-aminocaprolactam (54g) and L-arginine / L-phenylalanine zinc (5g) synthesized in (1). Then the feed port was closed. The nitrogen was reopened, the T-interface was opened, and nitrogen was introduced for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed and the temperature was started to rise. When the temperature reached 130°C, the temperature was stopped and stirring was started. The stirring was stopped after 20 minutes. Then react at 130°C for 6 hours, then heat to 140°C for 12 hours. The vacuum degree of the entire polymerization process is less than 50Pa. Then cool to room temperature, and then add 6L of chloroform. After complete dissolution, transfer the polymer solution to a 25L stainless steel barrel, add 12L of methanol to precipitate the polymer, filter, wash with ethanol 5 times, and place in a high vacuum oven at 80°C for 12 hours to obtain 905g of product.

[0091] (3) Product testing and analysis

[0092] According to the method in a specific embodiment of the present invention, the product is subjected to (1) molecular weight test (viscometry and GPC); (2) melting point (°C) test (DSC, TG); (3) mechanical property test: tensile strength (MPa) and elongation at break (%); (4) degradation performance test (degradation cycle, w; pH change); (5) cytotoxicity test (0-5 levels), value-added rate (%).

[0093] Test results:

[0094] (1) The weight average molecular weight is 23.8000 and the molecular weight distribution coefficient is 1.32

[0095] (2) Melting point (℃): 170

[0096] (3) Tensile strength (MPa): 38 and elongation at break (%): 29

[0097] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0098] (5) Cytotoxicity: Grade 0.

[0099] Example 2 (same as Example 1, except that L-galactonic acid-1,4-lactone was used Substitute for L-gulonic acid-γ-lactone)

[0100] (2) Same as Example 1

[0101] (2) Use 50g L-galactonic acid-1,4-lactone Substitute L-gulonic acid-γ-lactone in Example 1.

[0102] (3) Same as Example 1

[0103] Test results:

[0104] (1) The weight average molecular weight is 24.5000 and the molecular weight distribution coefficient is 1.30

[0105] (2) Melting point (℃): 170

[0106] (3) Tensile strength (MPa): 48 and elongation at break (%): 33

[0107] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0108] (5) Cytotoxicity: Grade 0.

[0109] Example 3 (same as Example 1, except that D-galacturonic acid γ-lactone was used Substitute for L-gulonic acid-γ-lactone)

[0110] (1) Same as Example 1

[0111] (2) Use 49g D-galacturonic acid γ-lactone Substitute L-gulonic acid-γ-lactone in Example 1.

[0112] (3) Same as Example 1

[0113] Test results:

[0114] (1) The weight average molecular weight is 25.3000 and the molecular weight distribution coefficient is 1.29

[0115] (2) Melting point (℃): 169

[0116] (3) Tensile strength (MPa): 45 and elongation at break (%): 30

[0117] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0118] (5) Cytotoxicity: Grade 0.

[0119] Example 4 (same as Example 1 except that (R)-3-amino-2-caprolactam was used Substituting the DL-aminocaprolactam of Example 1)

[0120] (1) Same as Example 1

[0121] (2) Use 54 g (R)-3-amino-2-caprolactam DL-aminocaprolactam of Example 1 was substituted.

[0122] (3) Same as Example 1

[0123] Test results:

[0124] (1) The weight average molecular weight is 25.7000 and the molecular weight distribution coefficient is 1.29

[0125] (2) Melting point (℃): 170

[0126] (3) Tensile strength (MPa): 41 and elongation at break (%): 31

[0127] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0128] (5) Cytotoxicity: Grade 0.

[0129] Example 5 (same as Example 1, except using 2-amino-δ-valerolactam Substituting the DL-aminocaprolactam of Example 1)

[0130] (1) Same as Example 1

[0131] (2) Use 48g 2-amino-δ-valerolactam DL-aminocaprolactam of Example 1 was substituted.

[0132] (3) Same as Example 1

[0133] Test results:

[0134] (1) The weight average molecular weight is 262,000 and the molecular weight distribution coefficient is 1.35

[0135] (2) Melting point (℃): 166

[0136] (3) Tensile strength (MPa): 49 and elongation at break (%): 26

[0137] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0138] (5) Cytotoxicity: Grade 0.

[0139] Example 6 (same as Example 1, except for the different ratio of polymerized monomers)

[0140] (1) Same as Example 1.

[0141] (2) Preparation of lactone lactide polymer: A 10L ceramic reactor with a heating liner is introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen is continuously passed at this temperature for 15 minutes. Then the T-interface is closed and the nitrogen is stopped. The temperature is reduced to 30-50°C, and then the feed port is opened to add dried L-lactide (806g, 80%), L-gulonic acid-γ-lactone (100g, 8%), DL-aminocaprolactam (108g, 12%) and L-arginine / L-phenylalanine zinc (5g) synthesized in (1). Then the feed port is closed. The nitrogen is reopened, the T-interface is opened, and the nitrogen is passed for 15 minutes; further, the T-interface is closed, the nitrogen is turned off, and vacuuming is started. When the vacuum degree is less than 50Pa, the T-interface is closed and the temperature is started to rise. When the temperature reaches 130°C, the temperature is stopped and stirring is started. The stirring is stopped after 20 minutes. Then react at 130°C for 6 hours, then heat to 140°C for 12 hours. The vacuum degree of the entire polymerization process is less than 50Pa. Then cool to room temperature, and then add 6L of chloroform. After complete dissolution, transfer the polymer solution to a 25L stainless steel barrel, add 12L of methanol to precipitate the polymer, filter, wash with ethanol 5 times, and place in a high vacuum oven at 80°C for 12 hours to obtain 902g of product.

[0142] (3) Same as Example 1

[0143] Test results:

[0144] (1) The weight average molecular weight is 24.1000 and the molecular weight distribution coefficient is 1.31

[0145] (2) Melting point (℃): 165

[0146] (3) Tensile strength (MPa): 46 and elongation at break (%): 31

[0147] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0148] (5) Cytotoxicity: Grade 0.

[0149] Example 7 (same as Example 1, except for the different ratio of polymerized monomers)

[0150] (1) Same as Example 1

[0151] (2) Preparation of lactone lactide polymer: A 10L ceramic reactor with a heating liner is introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen is continuously passed at this temperature for 15 minutes. Then the T-interface is closed and the nitrogen is stopped. The temperature is reduced to 30-50°C, and then the feed port is opened to add dried L-lactide (958g, 95%), L-gulonic acid-γ-lactone (25g, 2%), DL-aminocaprolactam (27g, 3%) and L-arginine / L-phenylalanine zinc (5g) synthesized in (1). Then the feed port is closed. The nitrogen is reopened, the T-interface is opened, and nitrogen is passed for 15 minutes; further, the T-interface is closed, the nitrogen is turned off, and vacuuming is started. When the vacuum degree is less than 50Pa, the T-interface is closed and the temperature is started to rise. When the temperature reaches 130°C, the temperature is stopped and stirring is started. The stirring is stopped after 20 minutes. Then react at 130°C for 6 hours, then heat to 140°C for 12 hours. The vacuum degree of the entire polymerization process is less than 50Pa. Then cool to room temperature, and then add 6L of chloroform. After complete dissolution, transfer the polymer solution to a 25L stainless steel barrel, add 12L of methanol to precipitate the polymer, filter, wash with ethanol 5 times, and place in a high vacuum oven at 80°C for 12 hours to obtain 902g of product.

[0152] (3) Same as Example 1

[0153] Test results:

[0154] (1) The weight average molecular weight is 27.7000 and the molecular weight distribution coefficient is 1.29

[0155] (2) Melting point (℃): 172

[0156] (3) Tensile strength (MPa): 50 and elongation at break (%): 27

[0157] (4) Degradation cycle (w): 16; pH: 6.3-6.9

[0158] (5) Cytotoxicity: Grade 0.

[0159] Example 8 (same as Example 1, except for different catalyst content)

[0160] (1) Same as Example 1

[0161] (2) The amount of catalyst used in Example 1 is 7.5 g.

[0162] (3) Same as Example 1

[0163] Test results:

[0164] (1) The weight average molecular weight is 25.5000 and the molecular weight distribution coefficient is 1.31

[0165] (2) Melting point (℃): 171

[0166] (3) Tensile strength (MPa): 44 and elongation at break (%): 30

[0167] (4) Degradation cycle (w): 15; pH: 6.0-6.5

[0168] (5) Cytotoxicity: Grade 0.

[0169] Example 9 (same as Example 1, except that the catalyst is different from that in Example 1, and arginine is replaced by lysine)

[0170] (1) Catalyst preparation: Synthesis of L-lysine / L-phenylalanine zinc: Lysine (14.6 g, about 0.1 mol), L-phenylalanine (16.5 g, about 0.1 mol) and methanol (300 ml) were added to a 1 L three-necked flask, stirred and reacted in a 60°C constant temperature water bath for 20 min, guanidine carbonate (24 g, about 0.2 mol) was added, and 50 ml of deionized water was added until all dissolved, and then nitrogen was passed into the solution for 10 min to remove the oxygen in the solution and the reaction bottle, and 100 ml of a solution of zinc chloride in methanol water (methanol / water = 80 ml / 20 ml) (13.6 g, about 0.1 mol) was added in a nitrogen-filled environment. After the addition was completed in 30 minutes, the mixture was reacted at 60°C for 5 hours, cooled to room temperature, filtered, and the precipitate was washed with ethanol 4 times. The product was dried in a vacuum oven at 60°C for 24 hours to obtain 35 g. The moisture content after drying was less than 0.01%.

[0171] (2) Same as Example 1, except that 5 g of L-lysine / L-phenylalanine zinc was used as the catalyst.

[0172] (3) Same as Example 1.

[0173] Test results:

[0174] (1) The weight average molecular weight is 23.1000 and the molecular weight distribution coefficient is 1.33

[0175] (2) Melting point (℃): 167

[0176] (3) Tensile strength (MPa): 40 and elongation at break (%): 30

[0177] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0178] (5) Cytotoxicity: Grade 0.

[0179] Example 10 (same as Example 1, except that the catalyst is different from that in Example 1, and arginine is replaced by histidine)

[0180] (1) Catalyst preparation: Synthesis of zinc L-histidine / L-phenylalanine: Lysine (15.g, about 0.1mol), L-phenylalanine (16.5g, about 0.1mol) and methanol (300ml) were added to a 1L three-necked flask, stirred and reacted in a constant temperature water bath at 60°C for 20min, guanidine carbonate (24g, about 0.2mol) was added, and 50ml of deionized water was added until all dissolved, then nitrogen was introduced into the solution for 10min to remove oxygen in the solution and the reaction flask, and 100ml of a solution of zinc chloride in methanol water (methanol / water = 80ml / 20ml) (13.6g, about 0.1mol) was added in a nitrogen-filled environment, and after the addition was completed in 30 minutes, the mixture was reacted at 60°C for 5 hours, cooled to room temperature, filtered, and the precipitate was washed with ethanol 4 times, and the product was dried in a vacuum oven at 60°C for 24 hours to obtain 36g. The moisture content after drying was less than 0.01%.

[0181] (2) Same as Example 1, except that 5 g of L-histidine / L-phenylalanine zinc was used as the catalyst.

[0182] (3) Same as Example 1.

[0183] Test results:

[0184] (1) The weight average molecular weight is 25.3000 and the molecular weight distribution coefficient is 1.35

[0185] (2) Melting point (℃): 170

[0186] (3) Tensile strength (MPa): 45 and elongation at break (%): 25

[0187] (4) Degradation cycle (w): 12; pH: 6.0-6.5

[0188] (5) Cytotoxicity: Grade 0.

[0189] Comparative Example 1: Synthesis and Performance of Traditional PLA

[0190] A 10L reactor with a ceramic heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously passed at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 30-50°C, and then the dried L-lactide (1000g) and 5g of stannous octoate were added by opening the feed port. Then the feed port was closed. The nitrogen was reopened, the T-interface was opened, and nitrogen was passed for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed, and the temperature was started to rise. When the temperature reached 130°C, the temperature was stopped, and stirring was started. The stirring was stopped after 20 minutes. Then the reaction was carried out at 130°C for 6 hours, and then the temperature was raised to 140°C for 12 hours. The vacuum degree of the entire polymerization process was less than 50Pa. Then it was cooled to room temperature, and then 6L of chloroform was added. After complete dissolution, the polymer solution was transferred to a 25 L stainless steel barrel, and 12 L of methanol was added to precipitate the polymer. After filtering, it was washed with ethanol 5 times and placed in a high vacuum oven at 80°C for 12 hours to obtain 829 g of product.

[0191] The test method is the same as in Example 1

[0192] Test results:

[0193] (1) The weight average molecular weight is 55.3000 and the molecular weight distribution coefficient is 1.32

[0194] (2) Melting point (℃): 175

[0195] (3) Tensile strength (MPa): 50 and elongation at break (%) 4.5

[0196] (4) Degradation cycle (w): 60; pH: 2.5-4.5

[0197] (5) Cytotoxicity: Grade 1.

[0198] It has high molecular weight and high strength, but poor toughness, long degradation cycle, and low pH during degradation, which is not conducive to tissue growth.

[0199] Comparative Example 2: (same as Comparative Example 1, except that the catalyst is replaced with arginine phenylalanine zinc prepared by the present invention)

[0200] Test results:

[0201] (1) The weight average molecular weight is 27.3000 and the molecular weight distribution coefficient is 1.33

[0202] (2) Melting point (℃): 169

[0203] (3) Tensile strength (MPa): 380 and elongation at break (%) 4.5

[0204] (4) Degradation cycle (w): 60; pH: 2.5-4.5

[0205] (5) Cytotoxicity: Grade 0.

[0206] However, it has poor toughness, a long degradation cycle, and a low pH during the degradation process, which is not conducive to tissue growth.

[0207] Comparative Example 3: Same as Example 1, except that L-gulonic acid-γ-lactone was removed

[0208] Test results:

[0209] (1) The weight average molecular weight is 29.2000 and the molecular weight distribution coefficient is 1.33

[0210] (2) Melting point (℃): 168

[0211] (3) Tensile strength (MPa): 33 and elongation at break (%) 12

[0212] (4) Degradation cycle (w): 45; pH: 5.0-6.0

[0213] (5) Cytotoxicity: Grade 0.

[0214] Compared with Example 1, the degradation is slowed down, the degradation period is prolonged, and the toughness is reduced.

[0215] Comparative Example 4: Same as Example 1, except that DL-aminocaprolactam was removed

[0216] Test results:

[0217] (1) The weight average molecular weight is 27.3000 and the molecular weight distribution coefficient is 1.36

[0218] (2) Melting point (℃): 168

[0219] (3) Tensile strength (MPa): 35 and elongation at break (%) 15

[0220] (4) Degradation cycle (w): 60; pH: 2.5-4.5

[0221] (5) Cytotoxicity: Grade 0.

[0222] The toughness is lower than that of Example 1, and the pH of the degradation process is lower than that of Example 1.

[0223] Comparative Example 5: Same as Comparative Example 1, except that stannous octoate was used as a catalyst instead of zinc arginine phenylalanine

[0224] Test results:

[0225] (1) The weight average molecular weight is 58.3000 and the molecular weight distribution coefficient is 1.31

[0226] (2) Melting point (℃): 171

[0227] (3) Tensile strength (MPa): 52 and elongation at break (%) 25

[0228] (4) Degradation cycle (w): 24; pH: 5.0-6.5

[0229] (5) Cytotoxicity: Grade 1.

[0230] Stannous octoate has a highly efficient catalytic performance and can obtain polymers with higher molecular weights, but tin catalysts are more toxic to cells than zinc catalysts.

[0231] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A lactide polymer modified by aminolactam and saccharide lactone, characterized in that: The lactide polymer is polymerized from lactic acid or lactide as a first monomer, aminolactam as a second monomer and saccharide lactone or uronic acid lactone as a third monomer, and its main chain comprises lactic acid units, amino-amino acid units and saccharide ester or uronic acid ester units.

2. The lactide polymer according to claim 1, characterized in that The lactide polymer contains 98-70 mol% of lactic acid units, 1-15 mol% of amino-amino acid units, and 1-15 mol% of sugar ester or uronic acid ester units; Further, the lactic acid or lactide includes D-lactic acid, L-lactic acid, DL-lactic acid; at least one of D-lactide, L-lactide, and DL-lactide; the aminolactam includes at least one of DL-aminocaprolactam, 2-amino-δ-valerolactam, and (R)-3-amino-2-caprolactam; the sugar acid lactone or sugar acid lactone includes at least one of D-(-)-gulonic acid-γ-lactone, D-galactonic acid lactone, L-galactonic acid-1,4-lactone, and D-galacturonic acid-γ-lactone.

3. A method for preparing the aminolactam and saccharolactone modified lactide polymer according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of the catalyst: using basic amino acid, phenylalanine and zinc salt as raw materials to prepare a zinc complex of basic amino acid and phenylalanine; (2) Preparation of modified lactide polymer: Lactic acid or lactide as the first monomer, aminolactam as the second monomer, saccharide lactone or uronic acid lactone as the third monomer and the catalyst obtained in step (1) are added to a reaction kettle under the protection of nitrogen or inert gas, and reacted at 120-180° C. for 6-100 hours to obtain a lactide polymer modified by aminolactam and saccharide lactone.

4. The preparation method according to claim 3, characterized in that: The basic amino acid is at least one of lysine, histidine and arginine, and the zinc salt is zinc chloride or zinc sulfate.

5. The preparation method according to claim 3, characterized in that: The preparation of the catalyst in step (1) specifically comprises: reacting a basic amino acid and phenylalanine with an inorganic guanidine salt in a solvent at 50-80° C. under the protection of nitrogen or an inert gas to generate an organic guanidine salt of the basic amino acid and phenylalanine, then adding a water and / or alcohol solution of a zinc salt, reacting at 50-80° C. for 3-8 hours, and obtaining a zinc complex of the basic amino acid and phenylalanine.

6. The preparation method according to claim 3, characterized in that: The ratio of the total amount of basic amino acids and phenylalanine to the solvent is 1 (mol): 1-2 (L); Further, the molar ratio of the basic amino acid to phenylalanine is 1:0.8-1.2; Further, the molar ratio of the total amount of basic amino acids and phenylalanine to the inorganic guanidine salt is 1:0.5-1.2; Further, the molar ratio of the total amount of basic amino acids and phenylalanine to the zinc salt is 2:1; Furthermore, the solvent is at least one of water, methanol, ethanol, tetrahydrofuran, and dioxane; Further, the inorganic guanidine salt is guanidine carbonate; Furthermore, the method also includes filtering, collecting, washing and drying the obtained zinc complex of the basic amino acid and phenylalanine.

7. The preparation method according to claim 3, characterized in that: The molar ratio of lactic acid or lactide as the first monomer, aminolactam as the second monomer, and saccharide lactone or uronic acid lactone as the third monomer is 98-70:1-15:1-15; Furthermore, in step (2), the mass of the catalyst is 0.4-1.0% of the mass of the monomer; Further, the lactic acid or lactide includes at least one of D-lactic acid, L-lactic acid, DL-lactic acid; D-lactide, L-lactide, DL-lactide; The aminolactam comprises at least one of DL-aminocaprolactam, 2-amino-δ-valerolactam, and (R)-3-amino-2-caprolactam; The sugar acid lactone or sugar acid lactone includes at least one of D-(-)-gulonic acid-γ-lactone, D-galactonic acid lactone, L-galactonic acid-1,4-lactone, and D-galacturonic acid-γ-lactone.

8. The preparation method according to claim 3, characterized in that: The step (2) is carried out in an anhydrous and oxygen-free environment; Furthermore, before the heating reaction in step (2), the reaction kettle is evacuated; Furthermore, the reaction in step (2) is preferably carried out at 130-140° C., and the reaction time is preferably 16-32 hours; Further, the reaction includes reacting at 120-150° C. for 2-4 hours, then heating to 130-160° C. for 5-15 hours; Furthermore, step (2) further comprises adding a non-protonic solvent to the reactor to dissolve the harvested aminolactam and lactide polymer modified with saccharide lactone, and then precipitating and washing the polymer with a polar solvent and drying it.

9. Use of the lactide polymer modified by aminolactam and saccharolactone according to claim 1 or 2 or obtained by the preparation method according to claims 3-8 as a biodegradable material in the field of biomedicine.

10. An amino acid zinc complex used as a catalyst for the ring-opening polymerization of lactide and lactone, characterized in that The amino acid zinc complex is prepared as follows: using basic amino acid, phenylalanine and zinc salt as raw materials to prepare a zinc complex of basic amino acid and phenylalanine; Further, the basic amino acid is at least one of lysine, histidine and arginine, and the zinc salt is zinc chloride or zinc sulfate; Furthermore, the preparation of the catalyst specifically comprises: reacting a basic amino acid and phenylalanine with an inorganic guanidine salt in a solvent at 50-80° C. under the protection of nitrogen or an inert gas to generate an organic guanidine salt of the basic amino acid and phenylalanine, then adding a water and / or alcohol solution of a zinc salt, reacting at 50-80° C. for 3-8 hours, to obtain a zinc complex of the basic amino acid and phenylalanine; Further, the ratio of the total amount of basic amino acid and phenylalanine to the solvent is 1 (mol): 1-2 (L); Further, the molar ratio of the basic amino acid to phenylalanine is 1:0.8-1.2; Further, the molar ratio of the total amount of basic amino acids and phenylalanine to the inorganic guanidine salt is 1:0.5-1.2; Further, the molar ratio of the total amount of basic amino acids and phenylalanine to the zinc salt is 2:1; Furthermore, the solvent is at least one of water, methanol, ethanol, tetrahydrofuran, and dioxane; Further, the inorganic guanidine salt is guanidine carbonate; Furthermore, the method also includes filtering, collecting, washing and drying the obtained zinc complex of the basic amino acid and phenylalanine.